Real-life experience of efficacy and safety of bilastine in the refractory cases of chronic spontaneous urticaria and its effect on the quality of life of patients - Abhishek De; Kiran Godse; Dhiraj Dhoot; Aarti Sarda (Wolters Kluwer Medknow Publications, 2021)
Introduction: Second-generation H1-antihistamines (SGAHs) are the mainstay of treatment of chronic spontaneous urticaria (CSU). Bilastine, newer non-sedating SGAHs, was recently introduced in India after the approval of the Drugs Controller General of India. There is a paucity of evidence about the long-term efficacy and safety of Bilastine in Indian patients. We undertook this study to find the long-term efficacy and tolerability of Bilastine in patients with CSU in India. Materials and Methods: This retrospective chart analysis was conducted by analyzing electronic medical records from May 1, 2019, to March 20, 2020, to identify patients of CSU who were prescribed Bilastine. Adult patients, with CSU >6 months were included, who had an unsatisfactory response as per Urticaria Activity Score 7 (UAS7) to previous antihistamine therapies, and who continued treatment for at least 6 months were included. Treatment effectiveness was determined by retrospectively reviewing their UAS7 scores from their medical records and evaluating their scores at weeks 4, 8, 12, 16, 20, and 24. Also, DLQI was assessed and compared at baseline and week 24. Result: Forty-nine patients were found to fulfill the criteria and included in the study. At the end of 24 weeks, 51% of patients (n = 25) achieved complete treatment response (UAS = 0), whereas 49% of patients (n = 24) were labeled as well-controlled urticaria (UAS<6). At 24 weeks, the mean UAS7 score (1.35 ± 1.61) was statistically significant compared to the baseline score (20.2 ± 5.73). The mean score of DLQI was also reduced to 1.63 ± 1.18 at 24 weeks from 8.39 ± 2.49 at baseline (P-value <0.001). Conclusion: The study showed that in patients who had an inadequate response with commonly used antihistamines at a double dose or combined use, switching over to Bilastine resulted not only in relieving the symptoms of CSU but also improved the quality of life of the patients with CSU.